Pharmacokinetic and pharmacodynamic evaluation of daclatasvir, asunaprevir plus beclabuvir as a fixed-dose co-formulation for the treatment of hepatitis C - Esposito, Isabella (2018)
Introduction: Many reports have evaluated the clinical efficacy and safety of the fixed-dose all-oral combination of daclatasvir, asunaprevir, and beclabuvir (DCV-TRIO), which was approved in Japan in December 2016 for the treatment of hepatitis C genotype (GT)-1 infection. Areas covered: This article reviews the pharmacodynamic and pharmacokinetic properties of the DCV-TRIO combination. The topics covered include data regarding the drug’s absorption, distribution, metabolism, excretion, and antiviral activity strategies. Its therapeutic efficacy and safety in GT-1 infection from phase 2/3 clinical trials are also discussed. Expert opinion: The ideal regimen for the treatment of Hepatitis C virus infection should be potent, pangenotypic, Ribavirin-free, safe, co-formulated, and affordable. Considering these characteristics, DCV-TRIO is neither pangenotypic nor potent enough against GT-1a, regardless of the presence or absence of cirrhosis. Other potential limitations of this regimen are its dosification (twice-daily), and the fact that since it includes a protease inhibitor, it is contraindicated in decompensated cirrhosis. For these reasons, it has only been approved in Japan, where more than 70% of the patients are infected with GT-1b. However, this co-formulation might still have a place in the treatment of non-cirrhotic patients infected with GT-1b provided that massive access to treatment is facilitated.